2009
DOI: 10.1111/j.1476-5381.2009.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activity of cannabinoid‐2 (CB2) receptors plays an essential role in the protean agonism of (+)AM1241 and L768242

Abstract: Background and purpose: Cannabinoid-2 (CB2) receptor-selective agonists have shown anti-nociceptive activity in models of neuropathic and inflammatory pain, and the two agonists most widely used, (, have been suggested to be protean agonists. Here we investigated the role of the constitutive activity of CB2 receptors in (+)AM1241 and L768242 protean agonism. Experimental approach: Pharmacological profiles of CB2 receptor ligands were evaluated in Chinese hamster ovary cells expressing recombinant human (hCB2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 27 publications
(55 reference statements)
6
48
0
Order By: Relevance
“…This is in accordance with data in literature reports, except for GW405833, which is known as a partial agonist (determined in a cAMP assay) [106]. Probably this is due to GW405833 being a protean agonist, as described above [111].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in accordance with data in literature reports, except for GW405833, which is known as a partial agonist (determined in a cAMP assay) [106]. Probably this is due to GW405833 being a protean agonist, as described above [111].…”
Section: Discussionsupporting
confidence: 86%
“…In a rat neuropathic pain model, GW405833 showed inhibitory effects on the formation of gliosis and inhibited neuropathic pain [110]. GW405833 was recently described as being a protean agonist [111]. As stated in the introduction, the CB 2 R is constitutively active, meaning a fraction of the receptor population attains spontaneously the active confirmation in the absence of a ligand.…”
Section: Indole Derivativesmentioning
confidence: 98%
“…In our assay, GW405833 shows a 10-fold lower affinity for hCB 2 and behaved as an inverse agonist in our GTPgS assay. Our results are in accordance with those of Yao et al, who reported that GW405833 is a potent inverse agonist in both hCB 2 (16,29,30).…”
Section: Discussionsupporting
confidence: 83%
“…Culture splitting was performed by detaching the cells with 0.5% trypsin/EDTA, and cells were plated at different concentration (see below) and maintained in the incubator at 37°C with 5% CO 2 . The method employed for the generation of hCB2 and hmGluR1 transfected cell lines and their characterization was reported previously (Mancini et al 7 and submitted US patent, respectively).…”
Section: Cell Culturesmentioning
confidence: 99%